2022
DOI: 10.3390/jcm11040926
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Biologics on Refractory Eosinophilic Otitis Media Associated with Bronchial Asthma or Severe Uncontrolled CRSwNP

Abstract: Eosinophilic otitis media (EOM) is a difficult-to-treat otitis media characterized by eosinophilic accumulation in the middle ear mucosa and effusion. It is resistant to conventional treatments and strongly associated with asthma and chronic rhinosinusitis with nasal polyps (CRSwNP). The aim of our study is to evaluate the effectiveness of biologics drugs in the control of EOM. This is a retrospective no-profit real-life observational study, involving patients affected by refractory EOM and in treatment with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…Eosinophilic otitis media (EOM) was observed in 3/57 of our patients. We noticed a reduction in EOM associated symptoms (evaluated with the Otitis Severity Score proposed by Iino et al [ 21 ] and the Italian validated version of COMOT-15 [ 22 ]) and an improvement in pure tone audiometry-evaluated pure tone average (PTA), as recently published [ 23 ].…”
Section: Resultssupporting
confidence: 56%
“…Eosinophilic otitis media (EOM) was observed in 3/57 of our patients. We noticed a reduction in EOM associated symptoms (evaluated with the Otitis Severity Score proposed by Iino et al [ 21 ] and the Italian validated version of COMOT-15 [ 22 ]) and an improvement in pure tone audiometry-evaluated pure tone average (PTA), as recently published [ 23 ].…”
Section: Resultssupporting
confidence: 56%
“…This also corresponds with the normalization of eosinophil counts seen in this study after treatment with biologic therapy. The improvement in this subject cohort coheres with several recent smaller studies examining biologic therapies for confirmed eosinophilic otitis media (10–15). These previous studies have all been small series or case reports, but data are accumulating demonstrating improved symptoms in this challenging population.…”
Section: Discussionsupporting
confidence: 82%
“…Eosinophilic otitis media likely falls in this spectrum of diffuse type 2 eosinophilic inflammation, given comorbid asthma and nasal polyposis in the diagnostic criteria (8,9). In small studies and single case reports (10)(11)(12)(13)(14)(15), patients with concomitant otologic disease have improved after initiation of treatment with biologic therapy for their coexistent asthma and nasal polyposis, suggesting a common underlying role for eosinophilia in the manifestations of this disease. The aim of the present study is to compare the response of suspected eosinophilic otitis media to treatment with or without a targeted biologic therapy against IL-4, IL-5, or IL-13 signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Recent basic science research has led to significant advances in understanding the pathophysiological processes of disease. These processes define the endotype of a disease opening the way for the development of new diagnostic tools and innovative targeted treatments, especially in the rhinologic fields [ 33 , 34 , 35 , 36 , 37 , 38 ]. As has already happened for asthma and CRSwNP, and for many other autoimmune and oncological pathologies, the study of molecular biomarkers might help to develop new potential therapeutic target, and to improve an early diagnosis and a more accurate prognosis.…”
Section: Discussionmentioning
confidence: 99%